Inferência em grafos aleatórios exponenciais através de métodos MCMC - Lima, Guilherme Antonio Alves de (Universidade Federal de São Carlos, 2020)
In this work we study statistical inference methods for random graphs. In particular, we study the Exponential Random Graph Model and we study Bayesian estimator based on Markov chain Monte Carlo (MCMC) algorithm. We apply the inferential method to model the Brazilian Airport Network.

In this work we study statistical inference methods for random graphs. In particular, we study the Exponential Random Graph Model (ERGM) and we study a Bayesian inferential method based on Markov chain Monte Carlo (MCMC) algorithms. We apply the inferential method to model the Brazilian Airport Network.
Statistical inference for Exponential Random Graphs using MCMC methods
Keywords: Grafos Aleatórios Exponenciais; Inferência Bayesiana; ANAC; MCMC; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA::ESTATISTICA::INFERENCIA PARAMETRICA